Retinoic acid signalling in fibro/adipogenic progenitors robustly enhances muscle regeneration - Liang Zhao; Jun Seok Son; Bo Wang; Qiyu Tian; Yanting Chen; Xiangdong Liu; Jeanene M. de Avila; Mei-Jun Zhu; Min Du (EBioMedicine, 2020)
Background: During muscle regeneration, excessive formation of adipogenic and fibrogenic tissues, from their respective fibro/adipogenic progenitors (FAPs), impairs functional recovery. Intrinsic mechanisms controlling the proliferation and differentiation of FAPs remain largely unexplored. Methods: Here, we investigated the role of retinoic acid (RA) signalling in regulating FAPs and the subsequent effects on muscle restoration from a cardiotoxin-induced injury. Blockage of retinoic acid receptor (RAR) signalling was achieved through dominant negative retinoic acid receptor α (RARα403) expression specific in PDGFRα+ FAPs in vivo and by BMS493 treatment in vitro. Effects of RAR-signalling on FAP cellularity and muscle regeneration were also investigated in a high-fat diet-induced obese mice model. Findings: Supplementation of RA increased the proliferation of FAPs during the early stages of regeneration while suppressing FAP differentiation and promoting apoptosis during the remodelling stage. Loss of RAR-signalling caused ectopic adipogenic differentiation of FAPs and impaired muscle regeneration. Furthermore, obesity disrupted the cellular transition of FAPs and attenuated muscle regeneration. Supplementation of RA to obese mice not only rescued impaired muscle fibre regeneration, but also inhibited infiltration of fat and fibrotic tissues during muscle repair. These beneficial effects were abolished after blocking RAR-signalling in FAPs of obese mice. Interpretation: These data suggest that RAR-signalling in FAPs is a critical therapeutic target for suppressing differentiation of FAPs and facilitating the regeneration of muscle and other tissues. Funding: This study was supported by grants from the National Institutes of Health (R01-HD067449 and R21-AG049976) to M.D.